Accuracy of PET-choline in nodal staging of localized very high-risk prostate cancer - Nuno Dias; Gianmarco Colandrea; Francisco Botelho; Lara Rodriguez-Sanchez; Yann Barbé; Petr Macek; Xavier Cathelineau (Archivio Italiano di Urologia e Andrologia, 2022)
Objectives: Localized very high-risk prostate cancer (VHR PCa) has long suffered from the inex-istence of good lymph node staging methods other than invasive surgery, as computed tomogra-phy has low sensitivity for nodal disease. With the rising use of positron emission tomography (PET), it is clinically meaningful to know its value for these patients. Our goal was to evaluate the real-life diagnostic accuracy of PET Choline in nodal staging, comparing it with the gold standard of extended pelvic lymph node dissection (ePLND). Materials and methods: We reviewed data from a high-volume center, including patients with VHR PCa according to current NCCN guidelines who underwent community 18F-fluorocholine PET/CT; followed by ro-botic assisted laparoscopic prostatectomy (RALP) and ePLND between 2010 and 2021. Results: We included 44 patients and 88 lymph node regions. Among those, 14/44 (31.8%) patients and 20/88 (22.7%) regions had nodal disease present on definitive pathology. In comparison with ePLND, we found a sensitivity of 64.3% (95% CI, 39.2-89.4%), specificity of 83.3% (95% CI, 70.0- 96.7%), PPV of 64.3% (95% CI, 39.2-89.4%), and NPV of 83.3% (95% CI, 70.0-96.7%) for nodal disease on a patient-based analysis; and sensitivity of 35.0% (95% CI, 14.1-60.0%), specificity of 88.2% (95% CI, 80.6-95.9%), PPV of 46.7% (95% CI, 21.4-71.9%), and NPV of 82.2% (95% CI, 73.4-91.0%) on a region-based analysis. Conclusions: In our view 18F-fluorocholine PET/CT doesn’t meet the criteria to be a standard exam for pre-operative staging for patients with VHR PCa, mostly due to its low sensitivity. However, other radiotracers should continue to be investigated in this setting.